2019
DOI: 10.1108/ssmt-08-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SAC – x NiO nano-reinforced lead-free solder joint in an ultra-fine package assembly

Abstract: Purpose This study aims to investigate the NiO nano-reinforced solder joint characteristics of ultra-fine electronic package. Design/methodology/approach Lead-free Sn-Ag-Cu (SAC) solder paste was mixed with various percentages of NiO nanoparticles to prepare the new form of nano-reinforced solder paste. The solder paste was applied to assemble the ultra-fine capacitor using the reflow soldering process. A focussed ion beam, high resolution transmission electron microscopy system equipped with energy dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Wafer saw process is then followed by die attach process on a leadframe thru the formation of conductive eutectic alloy to enable contact to the substrate, which is an active terminal for the device. Die attach process may also be performed by other means, depending on the requirement of end products [15]. For example, solder attach is typically found in power packages to efficiently handle big current, while logic gate devices on the other hand used non-conductive epoxy since the substrate is not an active terminal.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Wafer saw process is then followed by die attach process on a leadframe thru the formation of conductive eutectic alloy to enable contact to the substrate, which is an active terminal for the device. Die attach process may also be performed by other means, depending on the requirement of end products [15]. For example, solder attach is typically found in power packages to efficiently handle big current, while logic gate devices on the other hand used non-conductive epoxy since the substrate is not an active terminal.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Lead-free solders have good mechanical and wettability properties, making them sound alternatives for electronics applications for lead-based solders, which exhibit adverse environmental challenges. Despite their comparative advantages, lead-free solders face reliability concerns, including mechanical and thermal fatigue (Che Ani et al , 2019; Zhang et al , 2010). Studies by many researchers in the past decade have shown that the microstructural contents of lead-free solders determine their plastic and creep behaviour during the thermal cycling process (Lin and Chu, 2005; Wiese and Wolter, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research papers have explored methods and parameters to enhance the quality and reliability of solder joints in reflow processes (Bachok et al, 2018;Che Ani et al, 2018a, 2018b, 2019Mohamed Muzni et al, 2023;Zhang et al, 2023). However, a noticeable gap exists in the optimization of laser soldering parameters.…”
Section: Introductionmentioning
confidence: 99%